2022
DOI: 10.3390/f13071137
|View full text |Cite
|
Sign up to set email alerts
|

Phenological Shifts of the Deciduous Forests and Their Responses to Climate Variations in North America

Abstract: Forests play a vital role in sequestering carbon dioxide from the atmosphere. Vegetation phenology is sensitive to climate changes and natural environments. Exploring the patterns in phenological events of the forests can provide useful insights for understanding the dynamics of vegetation growth and their responses to climate variations. Deciduous forest in North America is an important part of global forests. Here we apply time-series remote sensing imagery to map the critical dates of vegetation phenologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…The phenological advance of both deciduous tree and spring-flowering understory plants is supported by previous studies and suggests that rising spring temperatures could increase the length of the growing season in temperate deciduous forests (Monahan et al 2016; Melaas et al, 2018; Seyednasrollah et al, 2020; Moon et al, 2021; Li et al, 2022). However, while our finding that understory spring phenology is advancing faster than deciduous canopy trees under warmer temperatures at northern latitudes (42–46°N) agrees with a recent study (Alecrim et al, 2022), it is at odds with other studies conducted within the same region (Heberling et al, 2019; Lee et al, 2022).…”
Section: Discussionsupporting
confidence: 76%
“…The phenological advance of both deciduous tree and spring-flowering understory plants is supported by previous studies and suggests that rising spring temperatures could increase the length of the growing season in temperate deciduous forests (Monahan et al 2016; Melaas et al, 2018; Seyednasrollah et al, 2020; Moon et al, 2021; Li et al, 2022). However, while our finding that understory spring phenology is advancing faster than deciduous canopy trees under warmer temperatures at northern latitudes (42–46°N) agrees with a recent study (Alecrim et al, 2022), it is at odds with other studies conducted within the same region (Heberling et al, 2019; Lee et al, 2022).…”
Section: Discussionsupporting
confidence: 76%
“…Seven studies analyzed phenological changes as a result of climate change in North America. What they all have in common is the use of multispectral timeseries [106,[189][190][191][192][193][194], while the time periods examined ranged from 10 [194] to well over 30 years [192]. These studies focused on the influence of hydrologic cycles on phenology, which is influenced by precipitation and temperature.…”
Section: Trend Changementioning
confidence: 99%
“…Similar results to the Asian studies were found in North America. Friedl et al [189] identified thermal forcing as the main driver of spring phenology, while Li et al [191] found that the phenology of deciduous forests in North America has shown an advanced SOS and delayed EOS over the last two decades, driven by climate variability.…”
Section: Trend Changementioning
confidence: 99%
“…Temperature, precipitation and their interaction determine vegetation productivity of boreal forests [6,7]. In northern high latitudes, climate warming has been shown to advance spring budburst and delay autumn senescence, thereby increasing vegetation productivity [8][9][10]. The growth of coniferous trees is also precipitation-dependent, with enhanced aboveground biomass under increased precipitation [11,12].…”
Section: Introductionmentioning
confidence: 99%